Application of Law No. 35 of 2014 on Criminal Acts of Sexual Violence Involving Children - Fachria Muntihani (Jurnal Syntax Admiration, 2024)
The focus of this research is on criminal acts of sexual violence involving children as perpetrators and victims. The main problem in this study, namely the application of Law 35 of 2014 in the criminal act of sexual violence involving children as perpetrators and victims in PN Sungguminasa. The type of research used is Field Qualitative Research or field research, with a statutory and sociological approach. The source of this research data was obtained by observation, interview, and document review methods. Data processing techniques are carried out by pumping data, then processing qualitatively and described by explaining, deciphering, or providing an overview of the subject matter. Based on the results of the study, it is known that the application of Law No. 35 of 2014 in cases of sexual violence involving children in PN Sugguminasa has been implemented by the provisions in the legislation. Child perpetrators or victims have been given protection by applicable regulations. As for if there is a later discrepancy between the provisions in the law and its application, then it is based on the decision of the court with various considerations.